Deferred Tax Assets and Deferred Tax Expense Against Tax Planning Profit Management - -, Warsono (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2017)
The purpose of this study is to examine the probability of earnings management performed by Property and Real Estate companies listed in Indonesia Stock Exchange (BEI) in the period 2011-2015. How to do the management to influence the accounting numbers can be either profit management through deferred tax assets, deferred tax expense and tax planning in the financial statements. This paper examines the effect of deferred tax assets deferred tax burden, and tax planning to earnings management conducted by the company. Data of the research is to use secondary data from company financial statements that were downloaded from the official website of Indonesia Stock Exchange. Using sampling technique is performed by purposive sampling. The study population is the Property and Real Estate companies listed in Indonesia Stock Exchange in the period 2011-2015. The study take sample as many as 34 companies Property and Real Estate in the Stock Exchange in 2011-2015. Hypothesis testing uses multiple regressions with SPSS software version 22. The result shows that the Deferred Tax Assets positive and significant effect on earnings management; while deferred tax expense and tax planning significant negative effect on earnings management. Keywords: Assets, Deferred Tax Expense, Tax Planning, Profit Management